Confarreatio w ustawodawstwie pierwszych cesarzy rzymskich - Zabłocka, Maria (Prawo Kanoniczne, 1988)
The institution of confarreatio (as well as other ways of entry of a wife into the manus mariti) at the beginning of Principate became obsolete. It was how ever still indispensable since only people born of a marriage with confarreatio could be elected superior priests. That is why in the days of Tiberius (Tac. Ann. 4.16) — and not during the reign of Augustus as might G. I. 136 suggest — a change was introduced, in agreement with which probably all women, and nothing fewer than priests’ wives, concluding confarreatio were in manu mariti only sacrorum causa, and in the light of the civil law they were equalized with other women.